Sport injuries sustained by athletes with disability: A systematic review - Weiler, R.; Van Mechelen, W.; Fuller, C.; Verhagen, E. (Sports Medicine, 2016)
Background: Fifteen percent of the world`s population live with disability, and many of these individuals choose to play sport. There are barriers to sport participation for athletes with disability and sports injury can greatly impact on daily life, which makes sports injury prevention additionally important. Objective: The purpose of this review is to systematically review the definitions, methodologies and injury rates in disability sport, which should assist future identification of risk factors and development of injury prevention strategies. A secondary aim is to highlight the most pressing issues for improvement of the quality of injury epidemiology research for disability sport. Methods: A search of NICE, AMED, British Nursing Index, CINAHL, EMBASE and Medline was conducted to identify all publications up to 16 June 2015. Of 489 potentially relevant articles and reference searching, a total of 15 studies were included. Wide study sample heterogeneity prevented data pooling and meta-analysis. Results: Results demonstrated an evolving field of epidemiology, but with wide differences in sports injury definition and with studies focused on short competitions. Background data were generally sparse; there was minimal exposure analysis, and no analysis of injury severity, all of which made comparison of injury risk and injury severity difficult. Conclusion: There is an urgent need for consensus on sports injury definition and methodology in disability sports. The quality of studies is variable, with inconsistent sports injury definitions, methodologies and injury rates, which prevents comparison, conclusions and development of injury prevention strategies. The authors highlight the most pressing issues for improvement of the quality in injury epidemiology research for disability sport.